Morphological and molecular taxonomy of Jahnula dianchia sp. nov. (Jahnulales) from submerged wood in Dianchi Lake, Yunnan China - Shi Ke Huang (2018)
© 2018 German Mycological Society and Springer-Verlag GmbH Germany, part of Springer Nature In this study, we report the discovery of Jahnula dianchia sp. nov., a freshwater lignicolous fungus belonging to the order Jahnulales (Dothideomycetes, Ascomycota), from a submerged woody substrate from Dianchi Lake, Yunnan, China. Morphologically, this new taxon differs from other species of the genus in ascospore morphology; the ascospores of the new species are dark brown with mammiform apices. We also provide a phylogenetic tree showing the molecular relationships between the new taxon with the previously accepted Jahnula species. The analysis of combined ITS, LSU, and SSU sequence dataset places J. dianchia within the Jahnulales sister to J. sangamonensis. The phylogeny also shows the placement of both strains of J. dianchia in a well-supported independent sub-clade.